PENGEMBANGAN INDUSTRI RUMAH TANGGA BERDASARKAN PERSPEKTIF AKUNTANSI DAN PENGEMBANGAN PRODUKSI - Ni Putu Sri Mariyatni; I Gusti Ayu Asri Pramesti; Desy Purnami Singgih Putri (KRISNA: Kumpulan Riset Akuntansi, 2019)
One of the famous crafts in Bali is gringsing fabric which is made in a conventional way using natural dyes. This research is uses an approach method where the researcher provides assistance to craftsmen who still do not have bookkeeping or records related to income, expenses, production costs and loss profits, the provision of facilities and infrastructure owned by craftsmen is still limited such as equipment for spinning yarn, weaving equipment, not yet marketing system for brochures, websites or the like, providing raw materials for yarn, because it is very dependent on supply from Nusa Penida or the surrounding area and does not yet have a product catalog so tourists visiting only see the types or models available on display only. The results is showed that the number of assets owned by each household industry experienced an increase after the implementation of activities by 40 percent from the previous year. The sales turnover of each household industry has increased by 30 percent from the previous year. The number and type of product marketed has increased by 30 percent from the previous year. The utilization of labor from surrounding residents has increased by 30 percent from the previous year. The average number of products sold has increased by almost 50 percent from the previous period.